Determination of mineral location coordinates in geotechnology and mining enterprises - Ravshanov Zavqiddin Yahyo oʻgʻli; Joldasbayeva Aysulu Baxitbay qizi; Maulenov Nurlibek Axmet o’g’li; O‘telbayev Azizbek Alisher o‘g’li (Global Scientific Publishing, 2023)
Three types of GDS-based studies, namely studies on mine planning, operation, and environmental management, were examined to describe the role of GDS as a decision-making support tool in mine development. This review was conducted by classifying previous GDS-based studies into several subtopics that pertain to mine development activities and the range of environments to be managed.Geotechnical analysis plays an important role in determining mining method selection. Iron ore body is initially planned to be mined by using long hole mining method. Detailed geotechnical site investigation and laboratory work are carried out to assess the applicability of the selected mining method. Diamond-drilled borehole cores are logged and geotechnical characterization of rock mass units is conducted by assigning RMR89 and Q classification values to the basic rock units. Extensive laboratory test work is carried out to find the geotechnical material properties of the ore and the wall rocks. Based on the results of rock mass classification efforts, empirical stope dimensioning work and detailed numerical (finite element) modeling for the stability analyses of pillar-stope layouts and overall mine are conducted. Finally, it is concluded that planned long hole stope dimensions appear to be unsafe and drift and fill mining method appears to be more suitable for this project.
Keywords: Geotechnical research; Mining methods; rock characterization; long hole